Mozart: Clarinet Concerto - Lawson, Colin (Cambridge Cambridge University Press, 1996)
Mozart's Clarinet Concerto is of supreme importance as his last instrumental work. Yet there are a number of special problems surrounding the piece, since the autograph is lost and the unique instrument for which it was written has not survived. This book provides evidence of the development of the clarinet, Mozart's encounter with it, and the composition and subsequent reception of the Clarinet Concerto. An analysis of the work is complemented by discussion of performance practice and of surviving relevant instruments. Expertise from the author's colleagues contributes to some valuable appendices.
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; 18th Century (1701-1800); Concerto; Clarinet; Musical analysis; Vienna (Austria)